Concise review of the genus Durvillaea Bory de Saint-Vincent, 1825 - Velasquez, Marcel; Fraser, Ceridwen I.; Nelson, Wendy A.; Tala, Fadia; Macaya, Erasmo C. (My University, 2020)
The genus Durvillaea includes six currently accepted species, as well as two newly proposed species. Durvillaea spp. have a diplontic life cycle, lack a free-living gametophyte and have oogamous reproduction. All Durvillaea species require rocky substrate for attachment and wave-exposed environments. These "southern bull kelps" occur exclusively in the Southern Hemisphere and are important foundation species, in most cases controlling local community structure, influencing biodiversity, and providing food and habitat for other culturally and economically important species. Most species are non-buoyant and these have restricted geographic ranges, in some cases endemic to small oceanic islands. Buoyant members of the genus are more widespread, with one species (Durvillaea antarctica) found throughout the subantarctic, Chile, and New Zealand. This chapter summarizes the taxonomy, biology, and economic importance of Durvillaea species, with a focus on aspects relevant to their availability and productivity as crop plants. Systematics, distribution, ecology, life histories, population status, harvesting times, protection, management and chemical composition are covered. Much of the available data are for the species Durvillaea antarctica, D. willana, and D. potatorum. The techniques used in harvesting and the human uses of Durvillaea spp. (e.g., as food) are described, along with recommendations for harvest timing and methods.
Keywords: durvillaea; biology; harvest; population status; economic importance